Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Nhi
Xem chi tiết
Lihnn_xj
20 tháng 1 2022 lúc 16:19

You can refer this one:

Recycle/Reuse Your Books. ...
Ditch the Paper. ...
Buy a Water Bottle. ...
Turn Off Your Phone. ...
Recycle. ...
Avoid Public Transport When Possible. ...
Save Water. ...
Save Electricity.

Huyền ume môn Anh
20 tháng 1 2022 lúc 16:18

We should grow a lot of tree

Mai phuong vu thi
Xem chi tiết
Huỳnh Châu Giang
5 tháng 12 2015 lúc 12:03

Vì a*b=BCNN(a;b)*UCLN(a;b)

Suy ra: UCLN(a;b)=320/160=2

a=2*m

b=2*n

UCLN(m;n)=1

Ta có a*b=(2*m)*(12*n)=320

m*n*4=320

m*n=80

Nếu m=80 => a=160

n=1 => b=2

Nếu m=40 =>a=80

 n=2 => b=4

Nếu m=20 => a=40

 n=4 => b=8

Nếu m=16 => a=32

n=5 => b=10

 

Nguyễn Hoàng Châu
Xem chi tiết
HT.Phong (9A5)
28 tháng 6 2023 lúc 11:11

Bài 2: 

1) \(x^2-4=x^2-2^2=\left(x-2\right)\left(x+2\right)\)

2) \(1-4x^2=1^2-\left(2x\right)^2=\left(1-2x\right)\left(1+2x\right)\)

3) \(4x^2-9=\left(2x\right)^2-3^2=\left(2x+3\right)\left(2x-3\right)\)

4) \(9-25x^2=3^2-\left(5x\right)^2=\left(3-5x\right)\left(3+5x\right)\)

5) \(4x^2-25=\left(2x\right)^2-5^2=\left(2x+5\right)\left(2x-5\right)\)

6) \(9x^2-36=\left(3x\right)^2-6^2=\left(3x-6\right)\left(3x+6\right)\)

7) \(\left(3x\right)^2-y^2=\left(3x-y\right)\left(3x+y\right)\)

8) \(x^2-\left(2y\right)^2=\left(x-2y\right)\left(x+2y\right)\)

9) \(\left(2x\right)^2-y^2=\left(2x-y\right)\left(2x+y\right)\)

10) \(\left(3x\right)^2-9y^4=\left(3x\right)^2-\left(3y^2\right)^2=\left(3x-3y^2\right)\left(3x+3y^2\right)\)

HT.Phong (9A5)
28 tháng 6 2023 lúc 11:29

Bài 2: 

21) \(\left(\dfrac{x}{3}-\dfrac{y}{4}\right)\left(\dfrac{x}{3}+\dfrac{y}{4}\right)=\left(\dfrac{x}{3}\right)^2-\left(\dfrac{y}{4}\right)^2=\dfrac{x^2}{9}-\dfrac{y^2}{16}\)

22) \(\left(\dfrac{x}{y}-\dfrac{2}{3}\right)\left(\dfrac{x}{y}+\dfrac{2}{3}\right)=\left(\dfrac{x}{y}\right)^2-\left(\dfrac{2}{3}\right)^2=\dfrac{x^2}{y^2}-\dfrac{4}{9}\)

23) \(\left(\dfrac{x}{2}+\dfrac{y}{3}\right)\left(\dfrac{x}{2}-\dfrac{y}{3}\right)=\left(\dfrac{x}{2}\right)^2-\left(\dfrac{y}{3}\right)^2=\dfrac{x^2}{4}-\dfrac{y^2}{9}\)

24) \(\left(2x-\dfrac{2}{3}\right)\left(\dfrac{2}{3}+2x\right)=\left(2x-\dfrac{2}{3}\right)\left(2x+\dfrac{2}{3}\right)=\left(2x\right)^2-\left(\dfrac{2}{3}\right)^2=4x^2-\dfrac{4}{9}\)

25) \(\left(2x+\dfrac{3}{5}\right)\left(\dfrac{3}{5}-2x\right)=\left(\dfrac{3}{5}+2x\right)\left(\dfrac{3}{5}-2x\right)=\left(\dfrac{3}{5}\right)^2-\left(2x\right)^2=\dfrac{9}{25}-4x^2\)

26) \(\left(\dfrac{1}{2}x-\dfrac{4}{3}\right)\left(\dfrac{4}{3}+\dfrac{1}{2}x\right)=\left(\dfrac{1}{2}x-\dfrac{4}{3}\right)\left(\dfrac{1}{2}x+\dfrac{4}{3}\right)=\left(\dfrac{1}{2}x\right)^2-\left(\dfrac{4}{3}\right)^2=\dfrac{1}{4}x^2-\dfrac{16}{9}\)

27) \(\left(\dfrac{2}{3}x^2-\dfrac{y}{2}\right)\left(\dfrac{2}{3}x^2+\dfrac{y}{2}\right)=\left(\dfrac{2}{3}x^2\right)^2-\left(\dfrac{y}{2}\right)^2=\dfrac{4}{9}x^4-\dfrac{y^2}{4}\)

28) \(\left(3x-y^2\right)\left(3x+y^2\right)=\left(3x\right)^2-\left(y^2\right)^2=9x^2-y^4\)

29) \(\left(x^2-2y\right)\left(x^2+2y\right)=\left(x^2\right)^2-\left(2y\right)^2=x^4-4y^2\)

30) \(\left(x^2-y^2\right)\left(x^2+y^2\right)=\left(x^2\right)^2-\left(y^2\right)^2=x^4-y^4\)

⭐Hannie⭐
28 tháng 6 2023 lúc 12:30

Bài `3`

\(1,\left(2x+1\right)^2+\left(2x-1\right)^2\\ \left[\left(2x\right)^2+4x+1^2\right]+\left[\left(2x\right)^2-4x+1^2\right]\\ =4x^2+4x+1+4x^2-4x+1\\ =8x^2+2\)

\(2,-\left(x+1\right)^2-\left(x-1\right)^2\\ =-\left(x^2+2x+1^2\right)-\left(x^2-2x+1\right)\\ =-x^2-2x-1-x^2+2x-1\\ =-2x^2-2\)

\(3,\left(x+2y\right)^2-\left(x-2y\right)^2\\ =\left[\left(x+2y\right)+\left(x-2y\right)\right]\left[\left(x+2y\right)-\left(x-2y\right)\right]\\ =\left(x+2y+x-2y\right)\left(x+2y-x+2y\right)\\ =2x.4y=8xy\)

\(4,\left(3x+y\right)^2+\left(x-y\right)^2\\ =\left[\left(3x\right)^2+6xy+y^2\right]+\left[\left(x^2-2xy+y^2\right)\right]\\ =6x^2+6xy+y^2+x^2-2xy+y^2\\ =7x^2+4xy+2y^2\)

\(5,-\left(x+5\right)^2-\left(x-3\right)^2\\ =-\left(x^2+10x+5^2\right)-\left(x^2-6x+3^2\right)\\ =-x^2-10x-25-x^2+6x-9\\ =-2x^2+16x-34\)

\(6,\left(3x-2\right)^2-\left(3x-1\right)^2\\ =\left[\left(3x-2\right)+\left(3x-1\right)\right]\left[\left(3x-2\right)-\left(3x-1\right)\right]\\ =\left(3x-2+3x-1\right)\left(3x-2-3x+1\right)\\ =\left(6x-3\right)\left(-1\right)=-6x+3\)

`@ Kidd`

Nguyễn Nhi
Xem chi tiết
︵✰Ah
15 tháng 1 2022 lúc 9:44

1.what do you think about the environment in your town?
In my hometown , people are not aware of environmental protection, there are still many people who are unaware and throw their garbage out, besides, there are still people who pick up trash and throw it in the right place.

Chanh Xanh
15 tháng 1 2022 lúc 9:44

Every day on the news reports, the news is everywhere, saying phrases like melting ice, global warming, acid rain, global climate change or adding new lands to become industrial landfills. All are consequences of environmental pollution.

ph@m tLJấn tLJ
15 tháng 1 2022 lúc 9:46

My environment is small but very clean

Ahihi
Xem chi tiết
mori ran
Xem chi tiết
lê minh đức
11 tháng 11 2017 lúc 12:39

a, Ta có : \(\frac{15}{x-1}\in Z\Leftrightarrow x-1\inƯ_{15}=\left\{-15;-5;-3;-1;1;3;5;15\right\}.\)

\(\Rightarrow x=\left\{-14;-4;-2;0;2;4;6;16\right\}\)

b, Ta có : \(\frac{x+6}{x-1}=\frac{x-1+7}{x-1}=\frac{x-1}{x-1}+\frac{7}{x-1}=1+\frac{7}{x-1}\)

Mà 1 thuộc Z => \(\frac{7}{x-1}\in Z\Leftrightarrow x-1\inƯ_7=\left\{-7;-1;1;7\right\}\)

\(\Rightarrow x=\left\{-6;0;2;8\right\}\)

C, tự làm nha 

mori ran
11 tháng 11 2017 lúc 12:45

 .laf sao?

hongcoinenh
Xem chi tiết
Minh Phan
Xem chi tiết
LOVE TFBOYS
Xem chi tiết